Frequency and Indications of Cesarean Section in Females Undergoing Induction of Labor: A Cross-sectional Study at a Tertiary Care Hospital (Journal of Fatima Jinnah Medical University, 2024)
Background: Induction of labour is a method to increase the vaginal delivery rate in women in whom the spontaneous onset of labor does not occur or they need to be delivered before the estimated date of delivery. However, in literature, the frequency of cesarean section is reported to be high after induction and not much work has been done especially in local settings. So we conducted this study to attain the current extent of cesarean section after induction and its most common indications. This study determined the frequency of cesarean sections and identified their indications in females undergoing induction of labor.Patients and methods: This descriptive cross-sectional study was done in the Department of Obstetrics and Gynecology, Central Park Teaching Hospital, Lahore from March to September 2021. After IRB approval 100 females were included in the study who were induced with Prostaglandin E2. Informed consent was taken and mode of delivery was observed. In cases of cesarean section, indications were noted in proforma.Results: In this study, 40% of women had cesarean section and 60% underwent normal delivery. The most frequent indication was fetal distress (32.50%) followed by refusal for further dose (25%), failed induction (22.50%) and prolonged or obstructed labor (20%). The frequency of cesarean section was higher in younger primiparous (55%) and obese women (42.5%).Conclusion: This study concluded that the frequency of cesarean section is higher in women undergoing induction of labour. The most frequent indication was fetal distress followed by refusal for further dose and failed induction.
Keywords: Cesarean section; Induction; Labor; Failed induction; Fetal distress